atpD gene sequencing, multidrug resistance traits, virulence-determinants, and antimicrobial resistance genes of emerging XDR and MDR-Proteus mirabilis - Algammal, Abdelazeem M.; Hashem, Hany R.; Alfifi, Khyreyah J.; Hetta, Helal F.; Sheraba, Norhan S.; Ramadan, Hazem; El-Tarabili, Reham M. (Scientific reports, 2021)
Proteus mirabilis is a common opportunistic pathogen causing severe illness in humans and animals. To determine the prevalence, antibiogram, biofilm-formation, screening of virulence, and antimicrobial resistance genes in P. mirabilis isolates from ducks; 240 samples were obtained from apparently healthy and diseased ducks from private farms in Port-Said Province, Egypt. The collected samples were examined bacteriologically, and then the recovered isolates were tested for atp D gene sequencing, antimicrobial susceptibility, biofilm-formation, PCR detection of virulence, and antimicrobial resistance genes. The prevalence of P. mirabilis in the examined samples was 14.6% (35/240). The identification of the recovered isolates was confirmed by the atp D gene sequencing, where the tested isolates shared a common ancestor. Besides, 94.3% of P. mirabilis isolates were biofilm producers. The recovered isolates were resistant to penicillins, sulfonamides, β-Lactam-β-lactamase-inhibitor-combinations, tetracyclines, cephalosporins, macrolides, and quinolones. Using PCR, the retrieved strains harbored atp D , ure C , rsb A , and zap A virulence genes with a prevalence of 100%, 100%, 94.3%, and 91.4%, respectively. Moreover, 31.4% (11/35) of the recovered strains were XDR to 8 antimicrobial classes that harbored bla TEM , bla OXA-1 , bla CTX-M , tet A , and sul 1 genes. Besides, 22.8% (8/35) of the tested strains were MDR to 3 antimicrobial classes and possessed bla TEM , tet A , and sul 1genes. Furthermore, 17.1% (6/35) of the tested strains were MDR to 7 antimicrobial classes and harbored bla TEM , bla OXA-1 , bla CTX-M , tet A, and sul 1 genes. Alarmingly, three strains were carbapenem-resistant that exhibited PDR to all the tested 10 antimicrobial classes and shared bla TEM , bla OXA-1 , bla CTX-M , tet A, and sul 1 genes. Of them, two strains harbored the bla NDM-1 gene, and one strain carried the bla KPC gene . In brief, to the best of our knowledge, this is the first study demonstrating the emergence of XDR and MDR- P.mirabilis in ducks. Norfloxacin exhibited promising antibacterial activity against the recovered XDR and MDR- P. mirabilis . The emergence of PDR, XDR, and MDR-strains constitutes a threat alarm that indicates the complicated treatment of the infections caused by these superbugs.